The use of percutaneous thermal sensing microchips for non-invasive measurement of body temperature in foals during summer seasons in a subtropical region - H. Kang; A. Sole-Guitart; V.A. Mellor; J.B. Gaughan; R.R. Zsoldos (Animal, 2022)
Continuous accurate attainment of the body temperature of foals is important to detect early stages of severe heat stress or fever due to a systemic illness. Among a number of methods to measure body temperature, measuring rectal temperature with a digital thermometer is most frequently used due to being relatively fast and simple method. It is also comparatively accurate and correlates well with the core body temperature. However, this method requires restraining the foal for a few seconds to obtain the temperature, and it can be dangerous for the handling person. Percutaneous thermal sensing microchips (PTSMs) are a means of monitoring the body temperature of horses, which offers a non-invasive, hygienic, quick, and accurate way to measure body temperature and provide an identification number for each individual, once it is implanted. This study tested the hypothesis that PTSM has a strong relationship with a conventional body temperature measurement, i.e., measuring rectal temperature with a digital thermometer of foals during summer seasons. Thirty-two foals in three consecutive foaling seasons (2018, 2019, and 2020 season) were implanted a PTSM into the right pectoral muscle, the right splenius muscle, the right gluteal muscle, and the nuchal ligament as early as two weeks after birth. The four PTSM temperatures, rectal temperature, and climate conditions (air temperature, relative humidity, and wet-bulb globe temperature) were obtained simultaneously during the three summer seasons and paired for comparison analysis. Among the PTSM temperatures, the pectoral muscle had the highest correlation and the least differences with rectal temperature. Using PTSM was safe, easy, and reliable for attaining body temperature in foals.